Peran Moderasi Gender dalam pengaruh Attitude, Norm Subjective dan Perceived Behavior terhadap Food Intention: Uji Empiris terhadap Konsumsi Makanan Tradisional - Setyawati, Ria; Milaningrum, Elisabeth; Simatupang, Lisnawaty (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2024)
One of the supporting efforts in the tourism sector is the culinary business because it can attract tourists to visit a tourist destination. In this regard, consumption, especially of local or traditional foods and beverages from a region, is seen as food with cultural values. Food is both a physical need and a cultural and social activity. Therefore, the objective of this research involves the role of gender as a moderation factor in the intention to consume traditional foods, considering factors such as attitude, subjective norm, and perceived behavior. This study involves students as tourist participants who prefer culinary tourism destinations they have visited. The research employs Structural Equation Modelling (SEM) analysis, utilizing Amos in this study. The research findings indicate that the moderating role of gender shows that gender does not moderate attitudes and subjective norms concerning the intention to consume traditional foods. However, it moderates perceived behavior regarding the intention to consume traditional foods.